Ultrathin high-temperature ferromagnetic rare-earth films: GdScGe and GdScSi monolayers - Wang, Rui; Hou, Lipeng; Shi, Puyuan; Cheng, Qianshuai; Zhang, Yungeng (Frontiers in Physics, 2023)
Two-dimensional ferromagnetism with robust room-temperature ferromagnetism has sparked intense interest for future miniature information storage devices. However, most two-dimensional ferromagnetic materials have a low Curie temperature. Here, by using density functional theory, two rare-earth monolayers, GdScSi monolayer and GdScGe monolayer, were predicted, in which these two monolayers exhibit ferromagnetic orders with large magnetic moments of about 7 B/Gd. Monte Carlo simulations predict the Curie temperatures are about 470 K and 495 K for 2D GdScSi monolayer and GdScGe monolayer, respectively. The spin band calculations show that they are metal. Besides, these two monolayers exhibit dynamical, mechanical, and thermal stabilities. The combination of these novel magnetic properties makes these 2D ferromagnetic crystals promising candidates for high efficiency spintronic applications.